2003
DOI: 10.1097/01.ccm.0000048620.88344.70
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin increases both protein and fluid microvascular permeability in cat skeletal muscle

Abstract: Endotoxin causes a significant increase in both protein and fluid microvascular wall permeability. These effects may explain the marked leakage of plasma to the interstitium that is often seen in critically ill patients with sepsis and systemic inflammatory response syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…This disruption is mediated by activation of PP2A [12]. Because endothelial barrier dysfunction contributes to morbidity in sepsis [25], there is an urgent need to identify the molecular mechanisms of this pathology and potential treatments. The present study discovered that intracellular ascorbate protects endothelial barrier function during septic insult and that this protection is associated with inhibition of oxidant production, PP2A activation, and occludin dephosphorylation and redistribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disruption is mediated by activation of PP2A [12]. Because endothelial barrier dysfunction contributes to morbidity in sepsis [25], there is an urgent need to identify the molecular mechanisms of this pathology and potential treatments. The present study discovered that intracellular ascorbate protects endothelial barrier function during septic insult and that this protection is associated with inhibition of oxidant production, PP2A activation, and occludin dephosphorylation and redistribution.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial barrier dysfunction occurs in systemic capillaries and venules of patients with sepsis. This dysfunction increases the microvessels’ permeability to macromolecules, such as albumin, and frequently leads to plasma extravasation, edema, organ failure and septic shock [25]. Since no effective pharmacological therapy is available to prevent the increase in permeability, there is a pressing need to identify the molecular mechanisms of this pathology and potential treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Endotoxin is known to stimulate the immune system in a dose-dependent manner [25]. Indeed, a marked increase in permeability in vivo has previously been shown in, for example, cats after intravenous administration of 1 mg/kg endotoxin [10]. On one occasion, an autointoxication with 1 mg of Salmonella endotoxin resulted in profound vasodilatory shock and a 15 l cumulative fluid balance over 72 hours in a laboratory worker [34].…”
Section: Discussionmentioning
confidence: 99%
“…These models have revealed that the microvasculature is exquisitely sensitive to the deleterious effects of sepsis [6] , [7] . The microvascular responses to sepsis or endotoxemia include impaired endothelium‐dependent vasodilatation [8] , oxidative stress [48] , increased endothelial cell adhesion molecule expression [6] , [7] , increased vascular permeability [23] , and the adhesion of leukocytes and platelets in postcapillary venules [12] , [22] . While one or more of these responses to sepsis have been demonstrated in the microvasculature of the mesentery, gut wall, and lung [12] , [22] , [30] , it remains unclear whether the cerebral microvasculature exhibits similar phenotypic changes during sepsis.…”
Section: Introductionmentioning
confidence: 99%